Effects of Servant Leader Behaviors on Organizational Citizenship Behaviors for the Individual (OCB-I) In the Nigeria’s Utility Industry Using Partial Least Squares (PLS) - Bambale, Abdu Ja’afaru; Shamsudin, Faridahwati Mohd; a/l Subramaniam, Chandrakatan (International Journal of Management and Sustainability, 2015)
This study examines the effects servant leader behaviors on employee organizational citizenship behaviors for the individual (OCB-I) among low and middle level employees of utility sector organizations in Nigeria. Specifically, this study examined the role of five servant leader behaviors - emotional healing, creating value for the community, conceptual skills, helping subordinates grow and succeed and putting subordinates first - on one major forms of employee citizenship behaviors - organizational citizenship behaviors that benefit the individual (OCB-I), A sample of 325 employees was used for empirical testing, and Partial Least Squares Method (PLS) algorithm and bootstrap techniques were used to test the hypothesized relationships. The results provided support for most of the hypothesized relationships except two. Specifically, emotional healing, conceptual skills, helping subordinates grow and succeed, putting subordinates first, are significantly and positively related to both OCB-I. However, creating value for the community is significantly but negatively related to OCB-I. Therefore, significant positive effects of emotional healing, conceptual skills, helping subordinates grow and succeed, and putting subordinates first suggest that the servant leader constructs are important in motivating followers’ OCB-I in organizations. Enhanced performance of OCB-I can improve the overall effective function of organizations. Contributions, limitations, and implications are discussed.